Dengue fever virus in Pakistan: effects of seasonal pattern and temperature change on distribution of vector and virus. (6th September 2016) - Bostan, Nazish; Javed, Sundus; Nabgha‐e‐Amen,; Eqani, Syed Ali Musstjab Akber Shah; Tahir, Faheem; Bokhari, Habib
Summary: Dengue fever is regarded as one of the most prominent emerging arboviral infections in Pakistan since its first epidemic almost 2 decades ago. Interplay between potential vectors, susceptible host, and lax environmental conditions may promote the infection, leading to an epidemic. These factors may indeed have played a major role in the spread of the disease in the country, which was limited to Karachi till 2006. With recent natural disasters such as the earthquake in 2005 and flooding in 2010, 2011 and 2012, numbers of vector‐borne diseases and outbreaks including dengue fever are on the rise in Pakistan. Therefore, it is a major concern for health sector workers and of utmost importance to have some understanding of the factors affecting disease outbreak for better risk assessment in the region. In the following report we review the climatic as well as host‐ and vector‐associated factors involved in the outbreak of dengue epidemics in Pakistan and highlight high‐risk zones in the country.